COMPARATIVE ANALYSIS OF HANDBALL CADETS AND YOUNGER CADETS IN THE MOTOR AND THE SPECIFIC-MOTOR SKILLS - Aldijana Muratović; Dobrislav Vujović; Danilo Bojanić; Georgi Georgiev (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Studies that deal with the problem of comparing two or more groups of handball players of different ages, are not so frequent. A number of Croatian authors contributed to these studies In a way that they have analyzed the differences between handball players at defferent levels of competition. In this study, a survey was conducted in order to determine whether there are differences between handball cadets and junior cadets in the motor and the specific motor skills. The sample in this study consisted of 30 handball players split in this way : the cadets (15), aged 16-17 years old and younger cadets (15) aged 13-14 years. There were 12 tests ( of measuring instruments) for estimating general motor abilities and 4 tests for estimating specific-motor skills. Basic statistical parameters were calculated for all the results in the variables. Statistically significant difference between the arithmetic means of cadets and junior cadets was determined by t-test for small independent samples. The data obtained from the testing of differences between group of handball cadets and junior cadets showed that the handball cadets had significantly better results in the four variables (long jump in here, throwing a handball ball from the gray straddle the ground, throwing a medicine ball from lying on back and the accuracy of jump shot from 9 m), while the younger cadets achieved significantly better results in the two variables (side steps and slalom in the area between 6-9 m). Since the results showed that handball cadets had better results (in a number of variables) than younger cadets , this study was consistent with the previous studies attempted to analyze the differences between handball players of different ages.